Evaluasi Penggunaan Pencuci Luka Terhadap Wound Healing: Literature Review - Paridah, Paridah; Tahir, Takdir; Yusuf, Saldy (Jurnal Keperawatan Muhammadiyah, 2019)
ABSTRACT Background : wound cleansing is part of wound management which performed to remove foreign bodies or pathogens that can cause infections in wounds to improve the wound healing process. Although it has been agreed that wound cleansing aims to reduce the incidence of infection but the reality is still debated among practitioners about the advantages and disadvantages of this implementation, so the selection of wound cleansers must be done wisely. This review literature aims to evaluate the use of available wound cleansers for wound healing. methods: Literatures was sourced from database Google scholar, PubMed, Proquest, ScienDirect, published from January 2011 to July 2018, there 14 articles were identified and after 9 filters were left. Results: from 9 articles that met the criteria, the results that showed the effect of wound cleansing use; Electrolyzed strong acid water, superoxidised, hydrogen peroxide, propylbetaine-polihesanide, povidine-iodine, chlorin dioxide, tap water with normal saline as a comparison group of the effectiveness in inhibiting infection, tissue toxicity, comfortably, timing and improvement of wound healing process. Based on the review results, it is generally stated that there is no significant difference between. Conclusions: There was no significant difference between wound cleanser. Based on this review it is recommended to pay attention to the type of wound before using wound Cleansing. Keywords: wound Cleansing, wound healing, literature review